Growing the virtual workplace the integrative value proposition for telework - Verbeke, Alain.; Schulz, Robert.; Greidanus, Nathan.; Hambley, Laura. (Edward Elgar, 2008)
Develops a EOS framework to examine both the interaction among employees, organizations and society, and the linkages among telework impacts, tracking, implementation and adoption. This book features an integrative framework for increasing telework adoption; practical tips - specific to each stakeholder; and an analysis of original survey data.